The Realization of Illocutionary Acts Found on TikTok Live Streaming - Budiono, Gracendy Aluz Clarita; Issy Yuliasri; Puji Astuti (English Education Journal, 2024)
TikTok is a social media that is currently becoming a trend center. One of TikTok's best features is live streaming with its mainstay content buying and selling. , commissive, directive, expressive, and declarative. Qualitative content analysis study was applied to analyze the illocutionary acts that appear in online communication via live streaming TikTok by the account @Carina's pen02. The data was collected through some stages including recording, transcribing, and classifying by using the SPEAKING (setting and scene, participants, endings, acts sequence, key, instrumentalities, norms, and genre) theory proposed by Dell Hyme (1972). Expert judgment was also involved in this study to guarantee the validity of the data. The four types of illocutionary acts were found in which the commissive is the most frequently used, followed by representative, directive, and expressive. Pragmatically, these findings improve understanding of speech acts in real-time digital interactions. Digital communications, it also provides strategies to increase audience engagement through the effective use of direction and expression. For online sellers, this research offers practical guidance on using persuasive language to build trust, drive sales, and maintain viewer interest during live streaming.